A newly designed entrance hood to reduce the micro pressure wave emitted from the exit of high-speed railway tunnel. (February 2021) - Kim, Dong Hyeon; Cheol, Seo Yong; Iyer, Rohit Sankaran; Kim, Heuy Dong
Highlights: Newly designed entrance hood bio-mimics shark gill ram ventilation technique. The maximum value of pressure gradient is reduced by 56% near the entrance. Micro-pressure wave emissions due to entrance hood installation is reduced by 78%. Newly developed analytical model predicts Micro-pressure waves at all frequencies. Abstract: Micro-pressure waves (MPWs) emitting from the exit of a railway tunnel pose a serious environmental hazard causing vibration and rattling of nearby structures. Consequently, with the advent of ever increasing train speeds, it has become extremely important for tunnel engineers and designers to control the emission of MPWs from the exit of a railway tunnel. The most economical and effective method known till date to reduce the magnitude of MPWs is by installing an aerodynamic hood at the entrance of a tunnel. Therefore, a newly designed entrance hood with air-slits attached on each side is studied in the current work. The air-slits are designed to bio-mimic the 'ram ventilation' technique used for respiration by hunter shark gills. These air-slits reduce the maximum value of the pressure gradient of the compression wave generated near the entrance. Thereby, a subsequent reduction in the maximum magnitude of MPWs emitted from the exit of tunnel is observed. A prototype of this entrance hood has been employed on a 1/64.2 reduced scale single track model tunnel and experimental tests were conducted using a model train with the nose shape of EMU-250 at two entry speeds of 180 km/hr. and 250 km/hr.. Pressure on the tunnel wall were measured at six different locations using a piezo-resistive pressure transducer and MPW at the tunnel exit were captured at three locations using a low-frequency sound level meter. A reduction in the pressure gradient of the compression wave and magnitude of MPW of about 56.3% and 78.7% respectively was observed with the installation of this entrance hood at a train speed of 250 km/hr. The obtained pressure transient data and the corresponding MPW values for both the train speeds are presented in detail with clear elucidations on the flow phenomena. Further, an analytical model to predict MPWs was developed using the solution of a vibrating circular piston in an infinite baffle plate. The predicted results of the analytical model when compared with the experimental values show a reasonably good match for the peak pressure magnitude and waveform of the MPW.